Ghostbusting : Which Output Gap Measure Really Matters? - Billmeier, Andreas (Washington, D.C. : International Monetary Fund, 2004)
This paper investigates various output gap measures in a simple inflation forecasting framework. Reflecting the cyclical position of an economy, an (unobservable) output gap has important implications for economic analysis. I construct and compare common output gap measures for five European countries. Since output above potential reflects domestic inflationary pressures, including a gap could improve the accuracy of autoregressive inflation forecasting. This assertion is tested in a simple simulated out-of-sample forecasting exercise for the period 1990-2002. The main conclusions are that an output gap rarely provides useful information and that there is no single best output gap measure across countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet